The Cooperative Principle: Is Grice’s Theory Suitable to Indonesian Language Culture? - Agnes Herawati (Lingua Cultura, 2013)
Article discussed how native speakers of Indonesian observed Grice’s maxims. One hundred conversations contributed in live talk show from varied Indonesia television channels were analysed. The results show that Grice’s maxims are fulfilled in many conversations. Nevertheless, in other situations, two kinds of non-fulfilment of the maxims are observed. First, the speaker deliberately exploits a maxim, which is suitable to Grice’s theory. Second, the speaker fails to observe but does not exploit a maxim, which leads to some interpretations of the cultural patterns of the Indonesian language: communicative politeness, high context culture and the needs of harmony in communication that are considered as the manifesting of Indonesian culture.